Infection prevention and control between legal requirements and German Society for Hygiene and Microbiology expert assessments: a cross-sectional study in september-november 2022 - Mardiko, Amelia A.; Buer, J.; Köster, A. M.; Kaba, H. E. J.; Mattner, F.; Zweigner, J.; Mutters, N. T.; von Maltzahn, N.; Leistner, R.; Eckmanns, T.; Brandt, Christian; Scheithauer, S. (The journal of hospital infection, 2023)
Background - In contrast to the beginning of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), pandemic, more and more hospital issues are now regulated by policy. - Aim - To identify differences between expert recommendations and legal requirements regarding infection prevention and control (IPC) strategies. - Methods - A cross-sectional study was conducted between 29th September 2022 and 3rd November 2022 addressing 1319 members of the German Society for Hygiene and Microbiology. The response rate was 12%. This paper reports the expert recommendations on different IPC strategies. - Findings - The majority (66%) of experts recommended universal mask usage, with 34% recommending it seasonally, even after the SARS-CoV-2 pandemic. Medical microbiology (MM) experts were more likely to recommend continuing to wear the masks indefinitely compared with IPC experts. Concerning the mask type, medical masks were recommended more frequently by IPC experts (47.3%), while FFP2 masks were preferred by MM experts (31.8%). The majority (54.7%) of experts recommended universal screening of employees, mainly in settings with extremely vulnerable patients and if regional incidence rates were high, at a frequency of twice per week. The dominant advice (recommended by at least 50% of experts) for employees exposed to SARS-CoV-2 was daily testing and wearing a mask, regardless of the length of exposure. - Conclusions - Expert recommendations deviate from the legal requirements and appear to be more differentiated and proportional. The influence of specific experience and expertise on mask recommendations should be investigated in more detail. For relevant policy decisions, a quick, focused and broad-based consultation of expertise could be of added value.
Online verfügbar 13 April 2023, Version des Artikels 2 June 2023
Gesehen am 28.09.2023